2015
DOI: 10.4187/respcare.03817
|View full text |Cite
|
Sign up to set email alerts
|

Precautionary Practices of Respiratory Therapists and Other Health-Care Practitioners Who Administer Aerosolized Medications

Abstract: Introduction Respiratory therapists and other healthcare workers are potentially exposed to a variety of aerosolized medications. The NIOSH Health and Safety Practices Survey of Healthcare Workers describes current exposure control practices and barriers to using personal protective equipment during administration of selected aerosolized medications. Methods An anonymous, multi-module, web-based survey was conducted among members of healthcare professional practice organizations representing respiratory ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 20 publications
0
13
0
5
Order By: Relevance
“…Due to the nature of their work, respiratory therapists can be exposed to an array of different compounds. Previous studies have reported healthcare workers (HCWs) experiencing side effects and airway irritation after the treatment of patients with aerosolized pentamidine, liposomal cisplatin, S&R isomers of Albuterol and ribavirin [12,14,15]. In certain circumstances, respiratory therapists can be also be exposed to experimental therapeutics used in the treatment of rare diseases or during global pandemics, the potential long-term side effects of which are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the nature of their work, respiratory therapists can be exposed to an array of different compounds. Previous studies have reported healthcare workers (HCWs) experiencing side effects and airway irritation after the treatment of patients with aerosolized pentamidine, liposomal cisplatin, S&R isomers of Albuterol and ribavirin [12,14,15]. In certain circumstances, respiratory therapists can be also be exposed to experimental therapeutics used in the treatment of rare diseases or during global pandemics, the potential long-term side effects of which are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The ratio of nasal cannula outer diameter to nostril inner diameter determines the leak of oxygen, and consequently aerosol from the system also. This ratio also plays a part in the delivered aerosol dose, as well as the levels of fugitive emissions to the local environment, which is a key, but often forgotten consideration for healthcare professionals or bystanders during aerosol therapy [ 46 , 47 , 48 , 49 ]. A recent review of aerosol delivery during HFNT by Li and colleagues provides additional insight into the factors at play [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chughtai et al (2013) showed that airborne medical aerosols are an occupational hazard to HCWs and homecare workers. Tsai et al (2015) highlighted the lack of knowledge among respiratory therapists with…”
Section: Accepted Manuscript Introductionmentioning
confidence: 99%